2010
DOI: 10.1038/nrgastro.2010.118
|View full text |Cite
|
Sign up to set email alerts
|

A new variant of bile duct duplication with coexistence of distal cholangiocarcinoma

Abstract: En bloc resection (including the duodenum, pancreatic head and adjacent lymph nodes), hepaticojejunostomy and pylorus-saving Whipple operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In our cases, biliary drainage was achieved by pylorus-preserving Whipple surgery and hepaticojejunostomy, an approach that has only been described once in the literature. 10 - 12 Both of our patients had an uneventful post-operative course.…”
Section: Discussionmentioning
confidence: 74%
“…In our cases, biliary drainage was achieved by pylorus-preserving Whipple surgery and hepaticojejunostomy, an approach that has only been described once in the literature. 10 - 12 Both of our patients had an uneventful post-operative course.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore this case appears to be a new variant not previously reported or classified. Literature review showed similar reported cases of inadvertent BDI associated with DBCD during surgery [6, 7] and other configurations that could not be classified with existing classification systems [3, 5, 8] [Fig. 4].…”
Section: Discussionmentioning
confidence: 87%
“…Recognition of the existence of this anomaly is important to prevent iatrogenic biliary injury and most importantly help in making the right surgical decision. After the first case of DCBD reported by Vesalius in 1543, numerous cases of different variants have been reported in the English literature across the globe [25]. Only seven out of nine variants currently described in the literature can be classified by available classification systems [4].…”
Section: Introductionmentioning
confidence: 99%
“…A and B coronal and axial magnetic resonance T2-weighted image showed the low signal septum in the dilated common bile duct which divided the extrahepatic bile duct into two parts, which connected to the left and the right hepatic duct respectively. C and D coronal maximum intensity projection magnetic resonance image and volume rendering image showed the dilated and duplicated common bile duct however, none of these were classified into classification system [8][9][10][11] (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%